Time Processing, Interoception, and Insula Activation: A Mini-Review on Clinical Disorders - Vicario, Carmelo Mario; Nitsche, Michael A.; Salehinejad, Mohammad A.; Avanzino, Laura; Martino, Gabriella (Frontiers in Psychology, 2020)
Time processing is a multifaceted skill crucial for managing different aspects of life. In the current work, we explored the relationship between interoception and time processing by examining research on clinical models. We investigated whether time processing deficits are associated with dysfunction of the interoceptive system and/or insular cortex activity, which is crucial in decoding internal body signaling. Furthermore, we explored whether insular activation predicts the subjective experience of time (that is, the subjective duration of a target stimulus to be timed). Overall, our work suggests that alteration of the interoceptive system could be a common psychophysiological hallmark of mental disorders affected by time processing deficits.